Dynamics of large wood added to Midwestern USA streams. (21st April 2021) - Bosio, Samuel F.; Shirey, Patrick D.; Entrekin, Sally A.; Hoellein, Timothy J.; Moerke, Ashley H.; Rosi, Emma J.; Tank, Jennifer L.; Lamberti, Gary A.
Abstract: Large wood (LW) additions are commonly used to restore degraded streams, particularly in regenerating forests that have low LW recruitment due to past logging. While the short‐term effects of LW input on stream structure and function are well studied, the long‐term dynamics of added wood are less documented. We assessed the long‐term movement and condition of LW added to three small (mean discharge, 28–47 L s −1 ) midwestern USA streams. In 2004, 25 aspen logs (2.5 m L × 0.5 m D) were added to 100‐m treatment reaches of three replicate streams in northern Michigan, USA, that contained low prior LW abundance. We monitored log movement and evaluated factors contributing to that movement over 14 years. Across all three streams, 41 of the 75 added logs moved downstream, with a mean travel distance of 4.0 m (SD, 7.0 m; n  = 75). However, all logs still remained within their original reaches. Most log movements occurred within the first 3 years following placement and were associated with high flow events. Individual log mobility was related to position in the channel; logs that were at least 70% submerged, and near horizontal in inclination, accounted for 83% of the single movements ≥0.5 m. In addition, after 14 years 32% of logs became part of aggregations and 86% displayed substantial decay. Our study suggests that restoration efforts that add LW to small, groundwater‐dominated streams can pose minimal risk to downstream reaches or human structures and may provide sustained ecological benefits to the ecosystem.